A risk assessment example for soil invertebrates using spatially explicit agent‐based models. (5th December 2015) - Reed, Melissa; Alvarez, Tania; Chelinho, Sónia; Forbes, Valery; Johnston, Alice; Meli, Mattia; Voss, Frank; Pastorok, Rob
ABSTRACT: Current risk assessment methods for measuring the toxicity of plant protection products (PPPs) on soil invertebrates use standardized laboratory conditions to determine acute effects on mortality and sublethal effects on reproduction. If an unacceptable risk is identified at the lower tier, population‐level effects are assessed using semifield and field trials at a higher tier because modeling methods for extrapolating available lower‐tier information to population effects have not yet been implemented. Field trials are expensive, time consuming, and cannot be applied to variable landscape scenarios. Mechanistic modeling of the toxicological effects of PPPs on individuals and their responses combined with simulation of population‐level response shows great potential in fulfilling such a need, aiding ecologically informed extrapolation. Here, we introduce and demonstrate the potential of 2 population models for ubiquitous soil invertebrates (collembolans and earthworms) as refinement options in current risk assessment. Both are spatially explicit agent‐based models (ABMs), incorporating individual and landscape variability. The models were used to provide refined risk assessments for different application scenarios of a hypothetical pesticide applied to potato crops (full‐field spray onto the soil surface [termed "overall"], in‐furrow, and soil‐incorporated pesticide applications). In the refined risk assessment, the population models suggest that soil invertebrate populations would likely recover within 1 year after pesticide application, regardless of application method. The population modeling for both soil organisms also illustrated that a lower predicted average environmental concentration in soil (PECsoil) could potentially lead to greater effects at the population level, depending on the spatial heterogeneity of the pesticide and the behavior of the soil organisms. Population‐level effects of spatial‐temporal variations in exposure were elucidated in the refined risk assessment, using ABMs and population‐level endpoints while yielding outputs that directly address the protection goals. We recommend choosing model outputs that are closely related to specific protection goals, using available toxicity data and accepted fate models to the extent possible in parameterizing models to minimize additional data needs and testing, evaluating, and documenting models following recent guidance. Integr Environ Assess Manag 2016;12:58–66. © 2015 SETAC Key Points: We demonstrate how mechanistic modeling of two common soil invertebrates can be used to refine risk assessment of plant protection products. Model results show how a protection goal can be addressed with the model, for example would soil invertebrate populations recover within one year following pesticide application. Population‐level effects depend on the spatial heterogeneity of the pesticide in soil and the behaviour of the soil organisms. Mechanistic models can add value to risk assessment by improving quantitative links between toxicity test endpoints and ecological protection goals.